2022
DOI: 10.46398/cuestpol.4072.51
|View full text |Cite
|
Sign up to set email alerts
|

Legal transformations in the Ukrainian legal system under the influence of international law

Abstract: The article is devoted to a topic as topical as the legal transformations in the Ukrainian system under the influence of international law. Therefore, the aim of the article is to discuss the theoretical and practical aspects of the study of the impact of international law on domestic law, as well as to identify the differences and similarities between international law and Ukrainian law in the specific field of criminal and civil law. The methodological basis of the study consisted in the use of the system-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The influence of international law on the national law of Ukraine in the field of criminal and civil law was the subject of study by Morska with the co-authors (Morska, et al, 2022), where the scientists concluded that when implementing certain provisions of acts of an international legal nature, the domestic legislator does not take into account the specifics of Ukrainian legislation regarding criminal liability.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of international law on the national law of Ukraine in the field of criminal and civil law was the subject of study by Morska with the co-authors (Morska, et al, 2022), where the scientists concluded that when implementing certain provisions of acts of an international legal nature, the domestic legislator does not take into account the specifics of Ukrainian legislation regarding criminal liability.…”
Section: Introductionmentioning
confidence: 99%